CHALLENGES FACED BY BUSINESS WHEN ADOPTING DIGITAL MARKETING STRATEGIES IN RURAL AREAS - Garg, Ankit Kumar; Singh, Chandan; Soni, Kartik; Agarwal, Pranjal; Tripathi, Shivam Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid advancement of digital technologies has transformed marketing strategies globally, offering businesses unprecedented opportunities to reach their target audiences. However, the adoption of digital marketing strategies in rural areas presents unique challenges that are often underestimated. This paper delves into the critical barriers that businesses face when attempting to implement digital marketing in rural regions. Key challenges identified include limited internet access, low levels of digital literacy, and resistance to change rooted in cultural differences. Additionally, the lack of infrastructure and resources in these areas further complicates the successful deployment of digital strategies. The paper also explores the difficulty of measuring the return on investment (ROI) in rural settings, where consumer engagement with digital content is often minimal. Through an analysis of these challenges, this study provides a comprehensive understanding of the obstacles that businesses must overcome to leverage digital marketing effectively in rural markets. The findings underscore the importance of tailored solutions, such as enhancing local digital infrastructure, improving digital literacy through partnerships, and adapting marketing content to local cultural contexts. The study concludes by suggesting actionable strategies that businesses can employ to mitigate these challenges, thereby maximizing the potential of digital marketing in rural areas.